2009
DOI: 10.3164/jcbn.08-233
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Radical Scavenging Activity of Human Colostrum, Transitional and Mature Milk

Abstract: Human milk from healthy women contains numerous nutrients such as antioxidants which are necessary for newborns. The aim of this study was to evaluate the changes of total antioxidant capacity (TAC) and free radical scavenging activity in human milk during the first six month period of lactation and also its relationship to maternal plasma. A total of 505 milk samples (colostrum, transitional and mature milks) collected from 115 healthy women with full term newborns. Blood plasma was obtained from 58 women at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
97
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(110 citation statements)
references
References 28 publications
(32 reference statements)
9
97
2
2
Order By: Relevance
“…On the other hand, antioxidant power which was measured by the bivalent-iron reduction method was higher in colostrum than in breastmilk in the other lactational periods. The same result was obtained by DPPH radical scavenging activity [24]. High level of antioxidant potential in colostrum may alleviate the oxidative stress of newborns with an immature antioxidative defense mechanism and then contribute to the growth and development of those newborns.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…On the other hand, antioxidant power which was measured by the bivalent-iron reduction method was higher in colostrum than in breastmilk in the other lactational periods. The same result was obtained by DPPH radical scavenging activity [24]. High level of antioxidant potential in colostrum may alleviate the oxidative stress of newborns with an immature antioxidative defense mechanism and then contribute to the growth and development of those newborns.…”
Section: Discussionsupporting
confidence: 69%
“…It was also reported that when antioxidant potential was measured by using the ABTS radical method, there was a positive correlation between antioxidant components in breastmilk and the antioxidant status of mothers and newborns [26]. Moreover, a study that evaluated maternal antioxidant status and antioxidant potential of breastmilk using the FRAP method also revealed a significant correlation between them [24]. Our study, too, revealed a correlation between maternal antioxidant status and antioxidant potential of breastmilk.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The scavenging capacity of DPPH was measured using the method proposed by Brand-Williams et al [12] with modifications proposed by Zarban et al [13], 50 μL of each HM sample was added with 1 mL DPPH in ethanol solution (0.06 mM). After homogenization, the mixture was allowed to stand for 30 minutes in a water bath at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies are based on the evaluation of antioxidant potential of HM [16] and CM [17], but little is known about the MM potential and the effect of period of lactation on it.…”
mentioning
confidence: 99%